2014
DOI: 10.1128/aem.04248-13
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer Potential of Outer Membrane Vesicles of Acinetobacter baylyi and Effects of Stress on Vesiculation

Abstract: dOuter membrane vesicles (OMVs) are continually released from a range of bacterial species. Numerous functions of OMVs, including the facilitation of horizontal gene transfer (HGT) processes, have been proposed. In this study, we investigated whether OMVs contribute to the transfer of plasmids between bacterial cells and species using Gram-negative Acinetobacter baylyi as a model system. OMVs were extracted from bacterial cultures and tested for the ability to vector gene transfer into populations of Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
197
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(211 citation statements)
references
References 80 publications
7
197
2
2
Order By: Relevance
“…Packaging of DNA into OMVs has been noted historically as a mechanism facilitating horizontal transfer of antibiotic resistance genes between Gram-negative bacteria (2426). Recent studies also report that RNA molecules are present in OMVs in marine ecosystems and in pathogenic Vibrio cholerae OMVs (2729).…”
Section: Resultsmentioning
confidence: 99%
“…Packaging of DNA into OMVs has been noted historically as a mechanism facilitating horizontal transfer of antibiotic resistance genes between Gram-negative bacteria (2426). Recent studies also report that RNA molecules are present in OMVs in marine ecosystems and in pathogenic Vibrio cholerae OMVs (2729).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, OMV-associated DNA is thought to be indiscriminately and externally bound to the vesicle. However, in a study investigating the capacity of Acinetobacter baylyi OMVs to enable horizontal gene transfer to A. baylyi and E. coli cells 93 , the location of DNA was carefully tracked using an antibody against double-stranded DNA. This analysis revealed that the DNA translocated from the cytoplasm into the periplasm and subsequently into OMVs, and that successful gene transfer required competence proteins in the recipient cell, suggesting that the OMVs lysed before DNA uptake by the recipient.…”
Section: Omv Functions In Bacterial Physiologymentioning
confidence: 99%
“…Stress included growth above the optimum temperature (Fulsundar et al, 2014), growth in minimal medium and extended periods in stationary and death phase between serial dilutions (90 h passages). We demonstrate for the first time growth phase-dependent costs and benefits of natural transformation in bacteria.…”
Section: Discussionmentioning
confidence: 99%